A review on surgical treatment options in gliomas - Yang, Zhongxi; Zhao, Chen; Zong, Shan; Piao, Jianmin; Zhao, Yuhao; Chen, Xuan (Frontiers in Oncology, 2023)
Gliomas are one of the most common primary central nervous system tumors and surgical treatment remains the principal role in the management of any grade gliomas. In this study, based on the introduction of gliomas, we review the novel surgical techniques and technologies in support of the extent of resection to achieve long-term disease control, summarize the findings on how to keep the balance between cytoreduction and neurological morbidity from a list of literature searched. The gliomas resection with modern neurosurgical techniques can be safely performed with low morbidity and extraordinary long-term functional outcomes.